Cpx Two-Component Signal Transduction in Escherichia coli: Excessive CpxR-P Levels Underlie CpxA* Phenotypes - De Wulf, Peter (American Society for Microbiology, 2000)
In Escherichia coli, the CpxA-CpxR two-component signal transduction system and the ς(E) and ς(32) response pathways jointly regulate gene expression in adaptation to adverse conditions. These include envelope protein distress, heat shock, oxidative stress, high pH, and entry into stationary phase. Certain mutant versions of the CpxA sensor protein (CpxA* proteins) exhibit an elevated ratio of kinase to phosphatase activity on CpxR, the cognate response regulator. As a result, CpxA* strains display numerous phenotypes, many of which cannot be easily related to currently known functions of the CpxA-CpxR pathway. It is unclear whether CpxA* phenotypes are caused solely by hyperphosphorylation of CpxR. We here report that all of the tested CpxA* phenotypes depend on elevated levels of CpxR-P and not on cross-signalling of CpxA* to noncognate response regulators.